Prediksi Pemakaian Obat Kronis Menggunakan Metode Monte Carlo - Jefri Rahmad Mulia; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2022)
The hospital is one of the places visited to get treatment services, the hospital also provides treatment services in the form of physical examinations, supporting examinations and also pharmaceutical services to get drugs. Pharmacy services in hospitals are run by a unit or installation which is generally called the Pharmacy Installation. Pharmacy installations must ensure that the supply of drugs is optimally met, so that there is no buildup or shortage of drug stocks. Drug supply management is very crucial because the Pharmacy Installation plays an important role in supporting hospital revenues. Good planning must also be accompanied by proper management and monitoring (controlling) of drug stocks and periodic evaluations. Technology support and information systems will facilitate the management team in planning, managing and monitoring and evaluating drug supplies. In order for the hospital to provide good service to patients, it is necessary for the hospital to have a supply of the drugs needed within a certain period of time so that the patient's medical needs can be met. This study uses data on chronic drug use in RSI. Siti Rahma Padang taken from 2017 to 2019. The data processed in the study were 12 types of drugs. Based on the analysis of these data, there are 5 types of chronic disease. Furthermore, the data is processed using the Monte Carlo algorithm. The result of testing this method is to get predictions of chronic drug use with the right level of accuracy. From the test results obtained 5 types of drugs whose accuracy level is above 80% and 7 types of drugs whose accuracy level is below 80% so that they can help RSI.Siti Rahma in making decisions in the future.